Do school-based smoking preventive interventions have unintended effects? Post hoc analysis of the Focus cluster randomised controlled trial - Susan Andersen; Lau C Thygesen; Charlotta Pisinger; Simone G Kjeld; Dina Danielsen; Marie P Jensen; Rikke F Krølner (BMJ Open)
Objectives Public health interventions are designed to improve specific health-related outcomes; however, they may also produce negative side effects, such as substitution use, psychological or social harms. Knowledge about the unintended effects of school-based smoking preventive interventions is sparse. Hence, this study examined these potential unintended effects of the smoking-reducing intervention, Focus, among students in the vocational education and training setting.Design Cluster randomised controlled trial stratified by school type with 5 months follow-up.Setting and participants Across Denmark, eight schools were randomised to the intervention group (n=844 students, response proportion 76%) and six schools to the control group (n=815 students, response proportion 75%). This study focused solely on students who smoked at baseline (N=491).Interventions The intervention was developed systematically based on theory and a thoroughly mixed-methods needs assessment. Intervention components included a comprehensive school tobacco policy (smoke-free school hours) supported by a 3-day course for school staff and launched by an edutainment session for students; class-based lessons and a quit-and-win competition; and individual telephone smoking cessation support.Outcomes Alternative tobacco and nicotine products (regular use of smokeless tobacco, hookah and e-cigarettes), regular cannabis use, boredom and loneliness at school, stress and perceived stigmatisation among smokers.Results We found no statistically significant unintended effects of the intervention. Nonetheless, insignificant findings indicated that students in the intervention group were less likely to be bored during school hours (OR 0.59, 95% CI 0.32 to 1.10) and experience stress (OR 0.62, 95% CI 0.35 to 1.10), but more likely to report feeling stigmatised compared with the control group (OR 1.55, 95% CI 0.71 to 3.40).Conclusions Overall, findings suggested no unintended effects of the Focus trial with respect to substitution use, psychological, nor group or social harms. Future research is encouraged to report potential harmful outcomes of smoking preventive interventions, and interventions should be aware of the possible stigmatisation of smokers.Trial registration number ISRCTN16455577.